FREIREAN CHALLENGES: DEMOCRACY, VIOLENCES AND DIALOGICAL PRAXIS IN CONTEMPORANEITY - Bezerra de Castro Magalhães, Silvana (Revista Desenvolvimento Social, 2021)
This paper is an interdisciplinary theoretical essay, that aims to discuss the current bases of Brazilian (anti) democratic society and how it engenders authoritarian and violent relations. The current Brazilian context has signaled a frightening picture marked by violent and anti-democratic relations in more diverse social sectors. From this very current issue, the concepts of democracy and democratic society are discussed as a necessary basis for the construction of dialogical relations in society as a whole and specifically in the educational pedagogical context. It presents a discussion based on Freire's theory and its broad and pertinent dimensions of dialogic and antidialogical relations that can be built in society as opposed to relations based on violence and the silencing of certain social sectors that are increasingly invisible. In a dialogue with other authors, the concepts of Freedom, utopia and humanization are discussed as the possibilities for transformation and struggle in times of violence and hatred.